KEMAMPUAN BERPIKIR MATEMATIS DALAM KONTEKS PEMBELAJARAN ABAD 21 DI SEKOLAH DASAR (Universitas PGRI Sumatera Barat, 2017)
Developing the mathematical thinking be authorized in the context of the current of meaningfull learning. Learning for 21st century paradigm replace that generally provide a broad space on the developmental aspects and student learning tasks as learning subject. The context appears as the implications of the development of high order thinking skills that need to be optimized in the learning process as learning principles in the curriculum of 2013. The purpose of this paper to explain the concepts and principles that can be developed related to the mathematical thinking in the context of 21st century learning. The principles of 21st century learning also become the foundation as one of the basic considerations in the process of benchmarking and the development of curriculum changes that will be applied. The mathematical thinking identified in 5 components, among others: (1) understanding of mathematics; (2) solving mathematical problems; (3) mathematical reasoning; (4) The mathematical connection; (5) mathematical communication. Affiliated to the five components that are interconnected is, the learning process that leads to the 21 century learning can go hand in hand in making them. Development of materials and processes which are affiliated with aspects of learning and development of students form the basis for determining the direction and purpose of education that lead to the learning process in the classroom. The results of the analysis of the content is based on theoretical studies indicate alignment between the development of the mathematical thinking the learning context of the 21st century requires the development of high-level thinking skills for students, especially in elementary school.